Design And Development Of High Sensitivity Erbium Doped Fiber Amplifier - Endut, Rosdisham (2003)

(untitled)
Various aspects concerning Erbium Doped Fiber Amplifiers (EDFA) for use in C-band transmission system were investigated through experimental work culminating in the design and implementation of three different C-band EDFA’s. The most promising being an EDFA utilizing double pass with tunable bandpass filter (TBF) amplification scheme. The configuration is a new approach to increase the sensitivity of the preamplifier before the signal is received by the receiver. This is because, limited sensitivity preamplifiers offered in the markets that limit the fiber optic link design. Thus, a new approach is desirable in solving the problem. In this thesis, new technique is proposed to increase the sensitivity up to 10dB. STM-1 and STM-4 Bit Error Rate (BER) test on SDH network was successfully conducted in a laboratory environment. The test showed that no error was introduced. Finally it is concluded that DPEDFA is reliable to be used as a device to realize high sensitivity preamplifier, as its realization would result in a huge increase in additional power budget with minimum installation and maintenance complexity and cost.